STRENGTHENING INSTITUTIONAL SYNERGY IN WASTE MANAGEMENT: CHALLENGES AND STRATEGIC SOLUTIONS - Wiranti; Naswar; Putri Regita Salsabila Oktaviani; Irma Idris (UKM Lembaga Penalaran dan Penulisan Karya Ilmiah Fakultas Hukum Universitas Hasanuddin, 2025)
This study is entitled